Numerical Study Of The Spatial Fractional Advection-Diffusion Equation - et. al., Swapnali Doley, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Here we discuss the advection-diffusion equation with diffusion fractional in one dimension. The study provides a Riemann-Liouville fractional derivative (RLFD) to obtain an implicit scheme of space fractional advection-diffusion equation (SFADE). The Von-Neumann techniques are illustrated for the stability and provided the implicit scheme is unconditionally stable under all condition and also a convergent. Numerical examples are illustrated the behavior of the fractional-order diffusion.